Effects of an integrative warm-up method on the range of motion, core stability, and quality of squat performance of young adults - Šćepanović, Tijana; Kojić, Miloš; Mikić, Mladen; Štajer, Valdemar; Ödek, Uğur; Penjak, Ana (Frontiers in Sports and Active Living, 2024)
This research aims to determine the effects of an integrative warm-up method on the range of motion in joints of the lower extremities, the strength of the stabilizer trunk muscles, and the quality of the basic movement patterns in older adolescents. The study sample consisted of 88 male students (age 20.1±0.5). They were randomly divided into four groups: one control group (CG) (n=17; 180.8±7.9cm; 82.3±8.3kg) and three experimental groups (EG): EG1 (n=23; 180.9±7.0cm; 78.5±9.5kg), EG2 (n=31; 182.2cm±7.3cm; 79.5±11.5kg), and EG3 (n=17; 183.3±4.9cm; 77.5±11.8kg). The participants were subjected to a 6-week experimental treatment: EG1 once, EG2 twice, and EG3 three times a week. The experimental treatment consisted of four sub-phases representing the integrative warm-up Method: 1) Inhibition (self-myofascial release using a foam roller); 2) Lengthening (Static stretching in a maximum range of motion position); 3) Activation (Positional isometrics muscle activation of the trunk and gluteus); 4) Integration (Integrated all the previous phases into one complex movement pattern). Based on the covariance analysis (ANCOVA), statistically significant treatment effects were observed and positive changes were determined in all experimental groups. The differences between groups were observed in the following variables: Overhead Squat Assessment (p=0.000; ŋ_p^2=0.318), range of motion of left hip flexion (p=0.000; ŋ_p^2=0.371), range of motion of right hip flexion (p=0.000; ŋ_p^2=0.051) and range of motion of right hip extension (p=0.051; ŋ_p^2=0.088), Double Leg Lowering Test (F=2.411; p=0.014; ŋ_p^2=0.014) and range of combined motion (plantar and dorsiflexion) of left ankle joint (p=0.000; ŋ_p^2=0.299). There was no significant difference in the Plank Test (F=1.007; p=1.007; ŋ_p^2=0.035), range of combined motion (plantar and dorsiflexion) of right ankle joint (p=0.088; ŋ_p^2=0.170) and range of motion of left hip extension (p=0.158; ŋ_p^2=0.060). The participants of CG statistically significantly differed from EG1, EG2, and EG3 in the squat performance after the applied treatment. The effect of the treatment was the occurrence of a transformational processes in almost all measured variables. It can be concluded that the integrative method is effective and applicable in practice for both young adults and recreational athletes.